أحكام عقد الرعاية التجارية - القرني، حسن بن صالح بن شلعان (جامعة الإمام محمد بن سعود الإسلامية, 2021)
يهدف البحث لتحرير التكييف الفقهي لعقد الرعاية التجارية وتحديد أركانه، وبيان حكم عقد الرعاية التجارية وضوابطه، ومعرفة حكم المعاوضة على عقد الرعاية التجارية وحكم تأبيده. وانتهيت إلى أن عقد الرعاية التجارية عقد مستحدث لم يذكره الفقهاء السابقون والمعاصرون، والراجح في تعريفه أنه اتفاق تجاري بين طرفين يلتزم فيه أحدها بتقديم دعم للآخر مقابل خدمات ترويجية، والراجح في تكييفه الفقهي أنه عقد إجارة، وأركانه ثلاثة، وهي: الصيغة وهي الإيجاب والقبول، والعاقدان وهما الراعي والمرعي، والمعقود عليه وهو العوض والمعوض، والراجح أنه عقد جائز وصحيح بعدة ضوابط وأهمها: أن يكون العوض المقدم من الراعي مشروعاً، وأن يكون الأمر المرعي مشروعاً، وأن تقدم الخدمات الترويجية لأمر مشروع، وأن تكون الخدمات الترويجية معلومة، وألا يكون فيها كذب أو غش أو تزوير أو تدليس، وألا يترتب عليها ضرر، وأما حكم المعاوضة على هذا العقد فهو الإباحة، وعقد الرعاية التجارية المؤبد إن كان العوض في العقد مبلغاً محدداً لكل المدة فلا يصح العقد، بخلاف ما لو كان العوض مبلغاً منضبطاً بالمدة فالراجح من أقوال الفقهاء هو الصحة. وأوصي أن تضع وزارة التجارة ضوابط لعقود الرعاية التجارية، وأن تتقي الله الجهات الراعية والمرعية فيما يصدرون للناس ضمن الخدمات الترويجية، وأن تعرض بنود العقد قبل إبرامه على جهات أو أفراد شرعيين.
The research aims at editing the doctrinal adaptation for commercial sponsorship defining its elements, indicating the provision of commercial sponsorship contract and its regulations in addition to knowing the provision of netting on commercial sponsorship contract and the provision of its perpetuation. I concluded that the commercial sponsorship contract is a new contract neither mentioned by former or modern scholars. The prevailing definition that it is a commercial agreement between two parties. one is committed to provide support to the other for promotional services. The prevailing opinion about its doctrinal adaptation that it is a lease contract with three pillars which are form، namely offer and acceptance, the contract, namely the sponsor and the sponsored and the subject of contract, namely compensation and compensated. The preponderant opinion that it is a correct and permissible contract with a number of regulations, the most important of these that The compensation offered by the sponsor should be legal, the sponsored object should be legitimate, the promotional services should be provided to legal things, the promotional services should be clear, it also shouldn’t contain any fabrication, cheating, forgery or deception and it also shouldn’t cause any damage. The provision of netting – type on this contract is permissibility. In the perpetuated commercial sponsorship، if the compensation in the contract is a fixed sum for all the duration, then the contract is not valid, otherwise if the compensation is a fixed amount on the duration then the scholars’ preponderant opinion that the contract is valid. I recommend that the ministry of commerce should develop regulations for the commercial sponsorship contract, the sponsors and sponsored should also fear God about things published to people listed under the promotional services. I also recommend that the terms of the contract should be submitted to legitimate authorities or individuals before it is concluded.
Keywords: عقود الرعاية -- المعاملات التجارية -- النوازل الفقهية -- الأحكام الشرعية -- الفقه الإسلامي